GPla Polymorphisms Are Associated with Outcomes in Patients at High Cardiovascular Risk - Rath, Dominik (Front Cardiovasc Med, 2017)
BACKGROUND: Platelet membrane glycoprotein receptors mediate thrombus formation. GP Ia/IIa is an essential platelet integrin receptor. Single-nucleotide polymorphisms (SNPs) of the GP Ia/IIa gene alter GP Ia/IIa expression; however, their influence on cardiovascular disease remains unclear. This study aimed to investigate the effect of the GP Ia/IIa SNPs rs1126643 and rs1062535 on clinical outcomes in a large collective including high-risk patients with cardiovascular disease. METHODS AND RESULTS: GP Ia SNP analysis was performed in 943 patients with symptomatic coronary artery disease. All patients were tracked for all-cause death, myocardial infarction, and ischemic stroke for 360 days. Homozygous carriers of the minor allele showed significantly worse event-free survival when compared with major allele carriers in the complete collective as well as in the subset of high-risk patients (carrying all of the following three risk factors: diabetes type II, hypertension, and hyperlipidemia). There was no significant difference in the subset of low-risk patients (carrying none of the three risk factors). CONCLUSIONS: GPla SNPs are associated with cardiovascular prognosis especially in high-risk patients. Identification of GPIa SNPs is of importance to tailor therapies in patients at already high cardiovascular risk.